Development and application of the overseas exchange willingness and demand survey questionnaire for medical students - Wang, Jingna; Ni, Haojie; Ma, Huan; Wang, Minyan; Shi, Yun; Ji, Conghua (Frontiers in Education, 2024)
Objective: There has been a significant increase in international student exchange in recent years, with medical students comprising a large proportion of international students. This study aimed to develop and validate a questionnaire, the Medical Student Overseas Exchange Willingness and Demand Survey Questionnaire (MS-OEWDSQ), to assess medical students' intentions to study abroad and explore the potential influencing factors. Methods: This study was conducted in three stages: item generation and scale development; pilot study; and examination of scale reliability and validity. The item pool for the questionnaire was compiled from a literature review, an assessment of other relevant questionnaires, and interviews with medical students. Descriptive statistics were generated, and correlation analysis was performed to analyse the questionnaire data. The reliability of the measure was examined according to its internal consistency and split-half reliability. Exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) were used to determine the factor structure and test the construct validity.The final version of the MS-OEWDSQ comprised three factors with a total of 14 items. The total Cronbach's α coefficient of the questionnaire was 0.844, and the total split-half reliability coefficient was 0.639. This study also identified several factors that may affect medical students' willingness to go abroad for exchange. Specifically, education 2 删除[小葱]:(p<0.05) and foreign language level (p<0.05) were associated with the MS-OEWDSQ score, providing directions for future related research. Conclusions: This study developed and validated a questionnaire to measure medical students' willingness and demand for overseas exchange. This measure provides a powerful tool for evaluating whether medical students are willing to participate in overseas exchange. The questionnaire can be employed to help medical students self-test their intention to study abroad and to help medical colleges provide more accurate support and assistance to students who intend to study abroad.